2016
DOI: 10.1111/jomf.12348
|View full text |Cite
|
Sign up to set email alerts
|

Own‐Choice Marriage and Fertility in Turkey

Abstract: Goode’s foundational work on the fertility transition identified own-choice marriage as a factor driving fertility decline, part of a widening repertoire of choice pertaining to marriage and childbearing. Yet research supporting this connection in today’s transitional societies is scarce and somewhat contradictory, and it is unclear how other marital traditions, such as consanguineous marriage, shape this relationship. This study evaluates Goode’s theorized connection using pooled Demographic and Health Survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
0
1
Order By: Relevance
“…Hence, as measured here, the effect of the family of origin on fertility does not seem to be very strong. This finding contradicts earlier evidence from other studies on non-migrant populations (Tunc ¸bilek and Koc ¸1994; Murphy and Wang 2001;Steenhof and Liefbroer 2008;Rijken and Liefbroer 2009;Kolk 2014;Manglos-Weber and Weinreb 2016). Finally, we found that controlling for family background factors and individual socio-demographic characteristics hardly helped to explain the observed fertility differences between the migrants and the stayers.…”
Section: Discussioncontrasting
confidence: 99%
“…Hence, as measured here, the effect of the family of origin on fertility does not seem to be very strong. This finding contradicts earlier evidence from other studies on non-migrant populations (Tunc ¸bilek and Koc ¸1994; Murphy and Wang 2001;Steenhof and Liefbroer 2008;Rijken and Liefbroer 2009;Kolk 2014;Manglos-Weber and Weinreb 2016). Finally, we found that controlling for family background factors and individual socio-demographic characteristics hardly helped to explain the observed fertility differences between the migrants and the stayers.…”
Section: Discussioncontrasting
confidence: 99%